Magnetic and luminescent hybrid nanomaterial based on Fe(3)O(4) nanocrystals and GdPO(4):Eu(3+) nanoneedles - Runowski, Marcin (Springer Netherlands, 2012)
ABSTRACT: A bifunctional hybrid nanomaterial, which can show magnetic and luminescent properties, was obtained. A magnetic phase was synthesized as a core/shell type composite. Nanocrystalline magnetite, Fe(3)O(4) was used as the core and was encapsulated in a silica shell. The luminescent phase was GdPO(4) doped with Eu(3+) ions, as the emitter. The investigated materials were synthesized using a coprecipitation method. Encapsulated Fe(3)O(4) was “trapped” in a nano-scaffold composed of GdPO(4) crystalline nanoneedles. When an external magnetic field was applied, this hybrid composite was attracted in one direction. Also, the luminescent phase can move simultaneously with magnetite due to a “trapping” effect. The structure and morphology of the obtained nanocomposites were examined with the use of transmission electron microscopy and X-ray powder diffraction. Spectroscopic properties of the Eu(3+)-doped nanomaterials were studied by measuring their excitation and emission spectra as well as their luminescence decay times. GRAPHICAL ABSTRACT: [Image: see text]